PENGARUH PENERAPAN TEKNIK PASAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 14 PADANG - Laswita, Fatma; Zulfaneti, Zulfaneti; Febriana, Rina (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research is motivated by the students understanding of mathematical concepts are still low. This type of research is experimental, the research design pre eksperimental design : static group comparison. The population in this research is the students in grade VIII SMPN 14 Padang. Sampling was done by purposive sampling, that takes into account the characteristics of the students and teachers of mathematics are the same . Characteristic in question is the grade VIII.5 and VIII.6 an unruly class , noise . Nonetheless VIII.5 class and VIII.6 have good creativity , which is chosen as the experimental class is a class VIII.5 as VIII.6 control class. Instruments used in this study is the final test. Form of essay tests, results of the analysis items show about the final test reliable. The data analysis technique used is the one side test with the help of MINITAB software. Based on the results of the final test data analysis can be found P-value=0,002 is less than Î±=0,05, so that hypothesis is approved. It can be concluded that the students understanding of mathematical concepts by applying Teknik Pasar VIII.5 SMPN 14 Padang grade better than students understanding of mathematical concepts by applying conventional learning models VIII.6 grade SMPN 14 Padang.